Efektivitas World Bank dalam Menangani Kasus Gender-based Violence (GBV) di Pronvinsi Kivu Republik Demokratik Congo, 2014 - 2017 - Najiha, Naila; Pattipelohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Gender Based Violence (GBV) means violence within a heterosexual relationship, in which the male partner attacks their partner, the victims of this violence are mostly women and this term is integrated with the idea of ‘male superiority over women’. After Congo War II, mining sites in Kivu Province of the Democratic Republic of Congo (DRC) are mainly controlled by ex-combatants and armed groups. The mining sites become unregulated and dangerous where violations of human rights including GBV are rampant. GBV in Kivu Province have huge impacts on Human Security, especially on Health Security, Economic Security, and Personal Security. Therefore World Bank as world financial institution which promote and embody Human Security cooperate with DRC government to eradicate GBV in Kivu Province. World Bank then conduct program to tackle GBV cases in Kivu Province that will be the focus of this research. The Program that will be the focus of this research is DRC: Prevention and Mitigation of SGBV in North and South Kivu. This research analyze the effectiveness of World Bank’s programs using three main indicators of effectiveness: output, outcome, and impact.